The Relationship Between Religious Coping Style and Anxiety over Breast Cancer in African American Women - Bowie, Janice (Journal of religion and health, 2001)
In this study, we investigated the relationship between religious coping style and anxiety related to breast cancer and the use of mammography in a sample of African American women. We also assessed the relationship of breast cancer anxiety to related variables such as church affiliation and attendance, church teachings on health, and acceptance of those teachings.